Transformasi Konsep Hukum Zakat : Dari Tekstualisme Syariah ke Institusionalisasi Negara - Novita Ayu Fitri W.; Fayzah Nazmah; Muhammad Noor Aini; Daanii Rizky Mabrury; Muhammad Sulaiman; Ali Murtadho Emzaed (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study examines the transformation of zakat law from a purely textualist Sharia approach to its institutionalization within the framework of the modern state. The research is motivated by the evolving practice of zakat, which is no longer solely based on classical legal texts but is now regulated and managed institutionally by the state to ensure effective and equitable distribution. The aim of this study is to analyze the process and implications of this paradigm shift in zakat law. The research employs a qualitative method through literature review and normative legal analysis of zakat regulations in Indonesia. The main findings indicate that the institutionalization of zakat improves accessibility, transparency, and accountability, while also presenting challenges in maintaining alignment with core Sharia principles. The implications of this research are significant for policymakers and zakat institutions in developing an adaptive and sustainable zakat legal system.